Circulating levels of inflammatory cytokines and cytokine receptors in patients with ankylosing spondylitis: a cross-sectional comparative study. (March 2015) - Sveaas, SH; Berg, IJ; Provan, SA; Semb, AG; Olsen, IC; Ueland, T; Aukrust, P; Vøllestad, N; Hagen, KB; Kvien, TK; Dagfinrud, H
Abstract : Objectives: Insight into the most important inflammatory pathways in ankylosing spondylitis (AS) could be of importance in risk stratification and the development of treatment strategies. Therefore, we aimed to compare circulating levels of inflammatory biomarkers between AS patients and controls, and explore associations between these biomarkers and clinical measures of disease activity. Method: In a cross-sectional study, 143 AS patients were compared with 124 population controls. Blood samples were analysed by immunoassays for interleukin (IL)-6, IL-17a, IL-23, soluble tumour necrosis factor receptor 1 (sTNF-R1) and 2 (sTNF-R2), and osteoprotegerin (OPG). Disease activity was measured by the AS Disease Activity Score (ASDAS) and the Bath AS Disease Activity Index (BASDAI). Results: Analysis of covariance (ANCOVA) demonstrated elevated plasma levels of sTNF-R1 [geometrical mean 0.94 (95% CI 0.88–1.00) vs. 0.83 (95% CI 0.78–0.89) ng/mL, p < 0.01] and OPG (2.3, 95% CI 2.1–2.4 vs. 2.0, 95% CI 1.9–2.2 ng/mL, p = 0.02) and, although not significant, of IL-23 (122, 95% CI 108–139 vs. 106, 95% CI 93–120 pg/mL, p = 0.07) in AS patients vs. controls. More AS patients had a high level of sTNF-R2 than controls (22 vs. 1, p < 0.01). No differences between the groups were seen for IL-6 and IL-17a. In patients, no significant associations were seen between inflammatory markers and disease activity measures after adjusting for personal characteristics. Conclusion: Significantly higher plasma levels of sTNF-R1, sTNF-R2, and OPG and numerically but non-significantly higher levels of IL-23 were found in AS patients compared to controls, indicating that these cytokines and cytokine receptors are important inflammatory pathways. Clinical measures of disease activity were not significantly correlated with circulating inflammatory markers.